PENGARUH KUALITAS PELAYANAN PUBLIK TERHADAP KINERJA ORGANISASI (Studi Pada Dinas Kependudukan dan Catatan Sipil Kabupaten Minahasa Tenggara) - Kawahe, Lucky; Tulusan, Femmy; Kiyai, Burhanuddin (Sam Ratulangi University, 2016)
ABSTRACT: This study originated from the results of the pre-survey which found that the performance of the organization in the Department of Population and Civil Registration Minahasa sicapai Tengga yet optimal. This is presumably related to the quality of public services is still relatively low. Thus, this study aims to determine and quantify the effect of Organizational Performance against Public Service in the Department of Population and Civil Registration Southeast Minahasa Regency. Descriptive and quantitative approach applied to problem solving. Samples drawn by purposive sampling of respondents as many as 36 employees / service personnel, then spread Questionnaire (a questionnaire) and the results are analyzed by applying the techniques of regression and correlation analysis product moment.The research results presented as follows:The result of identification of variables showed that in general, both the variable quality of public services as well as organizational performance variables Department of Population and Civil Registration Southeast Minahasa Regency are in the category of 'high'. However, there are two dimensions of quality of public services have not achieved optimal, the empathy dimension and the dimension of direct evidence. This is due to the relative weakness of supervision conducted leadership.The quality of public services and very significant positive effect on organizational performance. Both variables have a linear patterned functional relationship and are contributive. If the improved quality of public services, it will boost the performance of the organization, particularly in the Department of Population and Civil Registration Southeast Minahasa Regency.Thus, it can be concluded that the proposed research hypotheses have been tested empirically enforceability as well as to justify the theory underlying terori. It is recommended that local governments streamline supervision attached, as well as training programs to improve the quality of public services and organizational performance.Keywords: Quality of public services, the performance of the organization